Analisis Strategi Pemasaran Dalam Membangun Brand Awareness Pada Usaha Mikro Kecil Menengah (Studi Kasus Pada Umkm Teras Jahe Pekayon Jaya Kota Bekasi) - Syafii, Syafii; Prihadini, Diana (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research was conducted at Teras Jahe MSMEs. Teras Jahe MSMEs is a business entity that operates in the micro, small, and medium sectors, focusing on producing and marketing various ginger-based products. This research aims to find out and analyze problems, obstacles, and efforts to overcome obstacles in marketing strategies to build Brand Awareness in Teras Jahe MSMEs. The method used in this research is descriptive qualitative. The problem experienced by Teras Jahe is that first, Teras Jahe is dominated by customers over 40 years old and this makes it difficult to socialize on social media, for example, information about promos, new menus, and new places, they tend to be comfortable in one place and are out of date with cyberspace. Having six branches in strategic locations and utilizing online platforms such as Gofood, Grabfood, and Shopee Food, Teras Jahe adopts an omnichannel approach to reach consumers. Through effective digital marketing on Instagram, Teras Jahe builds brand awareness with interesting and relevant content, despite facing challenges in reaching a younger demographic and competing in the online market. With flexible pricing strategies, tailored product offerings, and attractive promotions, Teras Jahe has achieved top of mind among its consumers, differentiating itself from competitors with a focus on quality and service. Continuous efforts in education, innovation, and consumer interaction demonstrate Teras Jahe's commitment to sustainable brand growth and development